Questions kids ask about famous people - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Answers such questions as Who was Joan of Arc?; What was Michaelangel famous for?; Who was the Red Baron?; Who was the first person to walk on the moon?